TAXTAKÓPIR RAYONÍ OYKONIMLERINIŃ LEKSIKA-SEMANTIKALÍQ QURAMÍ HÁM ONÍ KARTALASTÍRÍW - Baltabayev, О.О. (ILIM hám JÁMIYET, 2022)
This article has been studied geographically the oikonyms of Takhtakupir district of the Republic of Karakalpakstan. District oikonyms are studied in lexical-semantic groups. A map of Takhtakupir district's oikonyms on lexical-semantic features has been developed.